Hydrodynamic profile of young swimmers: Changes over a competitive season - Barbosa, Tiago M. (2020)
The aim of this study was to analyze the changes in the hydrodynamic profile of young swimmers over a competitive season and to compare the variations according to a well-designed training periodization. Twenty-five swimmers (13 boys and 12 girls) were evaluated in (a) October (M1); (b) March (M2); and (c) June (M3). Inertial and anthropometrical measures included body mass, swimmer's added water mass, height, and trunk transverse surface area. Swimming efficiency was estimated by the speed fluctuation, stroke index, and approximate entropy. Active drag was estimated with the velocity perturbation method and the passive drag with the gliding decay method. Hydrodynamic dimensionless numbers (Froude and Reynolds numbers) and hull velocity (i.e., speed at Froude number = 0.42) were also calculated. No variable presented a significant gender effect. Anthropometrics and inertial parameters plus dimensionless numbers increased over time. Swimming efficiency improved between M1 and M3. There was a trend for both passive and active drag increase from M1 to M2, but being lower at M3 than at M1. Intra-individual changes between evaluation moments suggest high between- and within-subject variations. Therefore, hydrodynamic changes over a season occur in a non-linear fashion way, where the interplay between growth and training periodization explain the unique path flow selected by each young swimmer.